Spin-dependent optical transitions in yttrium iron garnet. (5th February 2021) - Chen, Jiunn; Hsu, Hua-Shu; Lo, Fang-Yuh
Abstract: This study reviewed the electronic structure using density functional theory (DFT) and demostrated the transmission of optical magnetic circular spectrum in probing spin-dependent optical transitions in yttrium iron garnet (YIG). DFT + U results suggested that the t2 orbital of tetrahedral irons are polarized by exchange-splitting O(2 p ) bands. Such polarization was found to be essential for the kinetic exchange and magnetism in YIG. DFT + U results also identified the spin-polarized energy gaps in YIG. On the basis of the distinctions of Fe3 O4 [J. Chen et al, Phys. Rev. B, 98, 085 141 (2018)] and YIG in electronic band features along with their manifestations in an optical magnetic circular diachroism (OMCD) spectrum, a map of spin-dependent optical transitions in YIG is presented. Based on the analysis of OMCD spectra at room temperature, the majority-spin and minority-spin gap in YIG are determined to be 2.45 and 2.25 eV, respectively.